White Noise: Composition, Colonization, and Colour - Finn, Geraldine (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
This paper examines the links between Western music, Western metaphysics, and Western imperialism. Taking Derrida's reading of "White Mythology" and "Violence and Metaphysics" as its point of departure, the paper explores the relationship between the theories and practices of musical composition formalized in Europe in the eighteenth and finalized in the nineteenth century, and the theories and practices of race, racial differentiation, and empire that coincide(d) with it.